The Effect of Phaseolus radiatus Fertilizer at Media Culture to Density and Carotenoid Content oF Dunaliella salina - Ici Dianita; Saberina Hasibuan; Syafriadiman Syafriadiman (Jurnal Perikanan dan Kelautan, 2020)
Dunaliella salina is a group of green algae that produces pigment (chlorophyll and carotenoids) and used as live feed in hatchery especially for marine commodities. Nitrogen and phosphorus are needed by D. salina can be obtained from P. radiatus fertilizer. The purpose of this research is to know the effect and optimal dose of P. radiatus fertilizer to density and carotenoid content of D. salina. The research was conducted on March-May in the Natural Feed Laboratory, BBPBAP Jepara Central Java. The research method was used completely randomized design. The treatments used is P0 (control) (Walne 0,5 mL/L), and P. radiates fertilizer is treatments P1 (60 mL/L), P2 (120 mL/L),  P3 (180 mL/L), with 3 replicates. The density of D. salina cells is observed for ten days. Carotenoid measurement in the exponential phase using a spectrophotometer.The results showed that the P. radiatus fertilizer as a media culture gives an effect on the density andcarotenoid content of D. salina. Phaseolus radiatus fertilizer showed the best density and carotenoid content at dose 60 mL/L. The amount of density in the exponential phase was 476.67 x 104 cells/mL with a carotenoid content of 0.967 µg/mL.